Rethinking Digital Games (KULT_online, 2009)
In the series “Metabasis”, published by the Institut für Künste und Medien (IKM / University of Potsdam) at transcript, the anthology Game Over? Perspektiven des Computerspiels (Perspectives on the Computer Game) is dedicated to the description of digital games as a genuinely new medium. Writing at the intersection of media theory and game studies, the authors examine such diverse issues as the virtual graphics space, the visual phenomenology of digital games, the dispositifs of games and reader-response to games as described by the new category of “involvement”.